Koalicije preživetja v obdobju zatona časopisne industrije - Bembič, Branko (Javnost (Ljubljana), 2021)
Combining the sociological and political economy approach to journalism as labour the study examines the effects of the decline of newspaper industry on class struggles in the sector. By adopting in-depth interviews and document analysis and by using the theoretical-historical conceptualisation of the technical composition of newswork the case study of the Dnevnik d.d. reveals the increasing proletarization of journalists and other newsworkers. The study indicates that the historical divides by which management dominates and segments newsworkers on the basis of ideology of professionalism have been gradually fading away. Although the trade union is actively engaged in organising all Dnevnik workers they has not formed a political composition and establish themselves as a unified political force in class struggles. In the decline of newspaper industry the management has shifted the competitive pressures onto workers and used them to lock employees into a survival coalition, successfully neutralising the class conflict and securing a continuous accumulation of capital in the face of the gradual shutdown of the company.
Keywords: Delovna razmerja; Industrial relations; Journalism; novinarji; Novinarstvo; Profesionalizacija; Professionalization; slovenski časopisi